The Legal Policy of Decentralization in Strategic Natural Resource Management: Acceleration of Local Government Independence Pursuant to the Rule of Law Principle - Sulaiman, Sulaiman; Mastura, Mastura; Mumaddadah, Mumaddadah (CV. Social Politic Genius (SIGn), 2025)
This research is motivated by the emergence of a constitutional anomaly: the recentralization of strategic natural resource management authority, which undermines the principle of regional autonomy as mandated by Article 18 of the 1945 Constitution. Although Law Number 23 of 2014 has regulated the distribution of concurrent government affairs, the enactment of recent sectoral regulations, such as Law Number 6 of 2023 and Law Number 2 of 2025, has conversely pulled licensing and fiscal management authority back to the central government. This study aims to formulate a natural resource governance transformation model that integrates local government independence with the principle of national legal certainty across the forestry, mineral and coal, oil and gas, geothermal, and fisheries sectors. The research method employed is normative legal research using statute, conceptual, and case approaches, analyzed qualitatively and prescriptively. The results indicate systematic norm disharmony and fiscal barriers resulting from central intervention—such as the 0% royalty policy—which significantly reduces fiscal capacity and regional administrative authority. The research concludes that accelerating regional independence requires legal policy reconstruction by implementing the FPIC principle to synchronize rights and guarantee national legal certainty and regional investment stability. The implications of this research demand harmonizing sectoral regulations that respect regional attributive authority and strengthening legislative oversight functions to realize accountable natural resource governance within a just Rule of Law framework.